No “haughty and inaccessible ivory tower”: Laval University and Adult Education, 1930–1965 - McLean, Scott (Canadian Journal of Education / Revue canadienne de l'éducation, 2023)
Canadian universities today assert their social relevance through highlighting processes such as community engagement, knowledge mobilization, and the promotion of equity, diversity, and inclusion. Much can be learned about such processes through examining an era in which Canadian universities asserted their social relevance through another vocabulary: that of adult education and extension. This article provides a case study of adult education work undertaken at Laval University from 1930 through 1965. Through reconstructing programs and practices at Laval, this article offers insight into past and present efforts of universities to pursue educational objectives with which they are not traditionally associated. The article narrates an important chapter in Canadian educational history, and also elucidates five lessons of importance to contemporary educational scholars and leaders: beware of institution-centric thinking, know how you can help people make a living, partner with external organizations, play to your institutional strengths, and serve and learn from others.